An empirical contribution to Minsky's financial fragility: evidence from non-financial sectors in Japan. (28th August 2018) - Nishi, Hiroshi
Abstract: This study presents an empirical analysis to detect Minsky's financial fragility and its determinants in non-financial sectors in Japan, with particular attention on the differences between sectors and size. While post-Keynesian developed theoretical analyses of financial fragility for economic growth models, its empirical application is limited. Based on the financial fragility indices derived from a cash-flow accounting framework and Minsky's margins of safety, I detect the overall configuration and evolution of financial fragility (hedge, speculative and Ponzi) in Japan. Then, I detect the factors that determine the probability of being Ponzi finance using a panel logistic regression. The results show that although speculative finance dominates many sector and size categories, the evolution of hedge and Ponzi finance is diversified and the determinants of financial fragility differ by category in Japan.